THE USE OF DIGITAL TECHNOLOGY IN UNIVERSITY LEARNING THROUGH A BIBLIOMETRIC APPROACH - Salima Rayane Kadri; Assia Kadri; Imane Fantazi; Nadjwa El Afri (International Journal of Innovative Technologies in Social Science, 2024)
The article proposes a bibliometric analysis of digitalization in higher education. Based on research conducted in October 2023, the study explored 967 articles in the Web of Science (WOS) database. It highlights the growing importance of digitalization in higher education institutions and explores emerging trends in teaching practices and learning patterns. The study reveals a spike in publications in 2021-2022, likely in response to the COVID-19 pandemic and the transition to online learning. The most active countries in publications on the subject are Russia and Germany accounting for more than 45% of articles. In addition, the analysis of bibliographic networks identified collaborations between authors and the most cited articles, while the analysis of key terms highlighted important research topics such as e-learning and digitalization. This bibliometric study sheds valuable light on an abundant field of research at the heart of the current transformations in higher education. However, additional analyses are needed to follow the rapid evolution of digital education in all its richness and diversity.